2023
DOI: 10.1002/smll.202303012
|View full text |Cite
|
Sign up to set email alerts
|

Janus Dual Self‐Strengthening Structure of Bi2O3/Gd2O3 Nanofibrous Membranes for Superior X‐Ray Shielding

Abstract: Bi2O3/rare earth oxide biphasic absorbers are attractive for high‐efficiency X‐ray shielding due to the complementary X‐ray absorption effects. However, its application is severely hindered by poor interphasic contact. Here, a new Janus interface engineering strategy is reported for the construction of continuous and flexible Bi2O3/Gd2O3 crystal nanofibrous membranes (FJNMs) with micro/nano dual self‐strengthening interphasic adhesion. This strategy facilitates online micro‐interlocking between Bi2O3/Gd2O3 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Consequently, metal oxides incorporating high-Z elements such as bismuth oxide (Bi 2 O 3 ), tungsten oxide (WO 3 ), and copper oxide (CuO) have been extensively investigated and documented as viable substitutes for Pb in recent decades. Bi 2 O 3 , with its high Z-value (83), thermal stability, biocompatibility, low toxicity, and minimal environmental impact, has emerged as the most promising candidate material. Researchers have found that, when the X-ray energy closely matches the binding energy of the K -shell or L -shell electrons of the atom, known as the K / L absorption edge, resonance absorption occurs; therefore shielding efficiency sharply increases. The L absorption edge of Bi 2 O 3 is near 13 keV, and the K absorption edge is near 90 keV, which has a strong absorption effect for X-rays larger than 13 and 90 keV, but a weak X-ray absorption region in the energy range of 40–90 keV. Achieving high shielding efficiency for a single-component element across the 0–90 keV range is extremely challenging, if not impossible, due to the presence of absorption edges for each element.…”
mentioning
confidence: 99%
“…Consequently, metal oxides incorporating high-Z elements such as bismuth oxide (Bi 2 O 3 ), tungsten oxide (WO 3 ), and copper oxide (CuO) have been extensively investigated and documented as viable substitutes for Pb in recent decades. Bi 2 O 3 , with its high Z-value (83), thermal stability, biocompatibility, low toxicity, and minimal environmental impact, has emerged as the most promising candidate material. Researchers have found that, when the X-ray energy closely matches the binding energy of the K -shell or L -shell electrons of the atom, known as the K / L absorption edge, resonance absorption occurs; therefore shielding efficiency sharply increases. The L absorption edge of Bi 2 O 3 is near 13 keV, and the K absorption edge is near 90 keV, which has a strong absorption effect for X-rays larger than 13 and 90 keV, but a weak X-ray absorption region in the energy range of 40–90 keV. Achieving high shielding efficiency for a single-component element across the 0–90 keV range is extremely challenging, if not impossible, due to the presence of absorption edges for each element.…”
mentioning
confidence: 99%